Elevated Packed Cell Volume and Reduced Plasma Volume Association with Hair Loss in Young Adults - Abdullah, Abdulmunem Kurdi (American Journal of Bioscience and Clinical Integrity, 2026)
Hair loss represents a significant clinical and psychosocial concern affecting millions worldwide, yet the role of hematological parameters beyond classical anemia remains poorly understood. This cross-sectional pilot study investigated the hypothesis that elevated packed cell volume (PCV), indicative of reduced plasma volume, is associated with increased hair loss in young adults. Twenty-one participants (mean age 34.4 ± 11.6 years) with PCV values ranging from 38% to 60% (mean 47.8 ± 7.7%) were evaluated for hair loss, baldness, and smoking status. Hair loss was present in 64.3% (9/14) of participants, baldness in 21.4% (3/14), and active smoking in 57.1% (8/14). Independent samples t-tests revealed significantly higher mean PCV in participants with hair loss (50.67 ± 7.14%) compared to those without (40.67 ± 2.73%; t = 2.795, p = 0.016), and in participants with baldness (53.29 ± 7.13%) versus those without (45.07 ± 6.56%; t = 3.089, p = 0.009). Pearson correlation analysis demonstrated moderate-to-strong positive associations between PCV and hair loss (r = 0.628, p = 0.016), PCV and baldness (r = 0.666, p = 0.009), and PCV and smoking status (r = 0.655, p = 0.011). Critically, plasma volume percentage (calculated as 100−PCV) showed a significant negative correlation with hair loss (r =− 0.628, p = 0.016), supporting the hypothesis that reduced plasma volume impairs nutrient and oxygen delivery to hair follicles. Chi-square analysis revealed a strong association between smoking and hair loss (χ² = 10.370, p = 0.001). These findings provide novel preliminary evidence that elevated PCV within the normal-to-high physiological range, reflecting reduced plasma volume, is significantly associated with hair loss and baldness in young adults, and suggest that smoking may exacerbate this relationship through hemoconcentration and microvascular compromise.